THE RETURN OF GEOPOLITICS: THE ASCENSION OF BRICS - Carmona, Ronaldo (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The convergence of five big developing countries concerning their common national interest of rising in the International System is the amalgam that makes BRICS cohesive in front of the tempestous global transition to multipolarity. This essay, which aims to connect the moment and the present challenges of BRICS vis-à-vis the contemporary geopolitical scenario, is composed of three parts. In the first, we seek evaluating the results of the Fortaleza Summit in relation to the great uncertainties and the scenario of a geopolitical dispute that characterize the present transition in the International System. The second part seeks offering an interpretation of BRICS, observing its potentialities and limits; it also seeks presenting some theoretical marks through which we can analyze the BRICS. The third part proposes an analysis of how BRICS can be read bearing in mind the Brazilian aspiration to rise to the condition of a global power, as well as the repercussion of the participation as a BRICS member to the country’s geographic-strategic surroundings. Last but not least, some conclusions will be presented with a focus on the challenges remaining after the historic VI BRICS Summit of Fortaleza.